2010
DOI: 10.3354/meps08495
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns and nursery habitat of juvenile thresher sharksAlopias vulpinusin the Southern California Bight

Abstract: We investigated the potential use of open coastal habitat over the continental shelf as a nursery area for the common thresher shark Alopias vulpinus. Seven juvenile threshers were tracked using acoustic telemetry to determine their movement patterns and nursery habitat in the Southern California Bight (SCB). Tracked sharks occupied waters over the continental shelf 87% of the time. These waters had an average (± SD) sea surface temperature of 18.8 ± 1.6°C and chlorophyll concentrations that were an order of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
0
15
0
3
Order By: Relevance
“…Acoustic telemetry studies in the SCB have shown that juvenile common threshers generally utilize shallow waters over the continental shelf as a nursery habitat (Cartamil et al 2010a), while subadult and adult common thresher [i.e., >120 cm fork length (FL)] occur in deeper waters offshore of the continental shelf (Cartamil et al 2010b). Larger sharks made vertical excursions by day to depths of up to 220 m that were suggestive of foraging behavior, whereas nocturnal depths were generally limited to the upper 20 m of the water column and were strongly constrained by the depth of the thermocline.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic telemetry studies in the SCB have shown that juvenile common threshers generally utilize shallow waters over the continental shelf as a nursery habitat (Cartamil et al 2010a), while subadult and adult common thresher [i.e., >120 cm fork length (FL)] occur in deeper waters offshore of the continental shelf (Cartamil et al 2010b). Larger sharks made vertical excursions by day to depths of up to 220 m that were suggestive of foraging behavior, whereas nocturnal depths were generally limited to the upper 20 m of the water column and were strongly constrained by the depth of the thermocline.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common vertical movement patterns observed in pelagic ecosystems is diel vertical movement (DVM), which is typically characterised by a shallow or surface-oriented depth distribution during the night followed by a highly variable, or deep depth distribution during daylight hours (Brierley, 2014;Neilson & Perry, 1990). This movement pattern has been described in a broad range of marine species from plankton (Hays, 2003) and planktivores (Brunnschweiler & Sims, 2011;Klevjer, Torres, & Kaartvedt, 2012;Sims, Southall, Tarling, & Metcalfe, 2005) to tertiary consumers (Bazzino, Gilly, Markaida, Salinas-Zavala, & Ramos-Castillejos, 2010;Sims et al, 2006) and large predators (Andrews et al, 2009;Campana & Joyce, 2004;Cartamil, Wegner, Kacev, et al, 2010;Queiroz, Humphries, Noble, Santos, & Sims, 2010). Thermoregulation, oxygen limitation, predator avoidance, navigation during migrations, and foraging on diel migrating prey have all been suggested as drivers of DVM in pelagic predators (Campana et al, 2011).…”
mentioning
confidence: 99%
“…The movement patterns of blue and thresher sharks have previously been investigated in the Atlantic (Campana et al, 2011;Queiroz et al, 2010;Vandeperre et al, 2016;Vandeperre et al, 2014) and Pacific Oceans (Cartamil, Wegner, Aalbers, et al, 2010;Cartamil, Wegner, Kacev, et al, 2010;Musyl et al, 2011;Stevens et al, 2010). Satellite tagging of blue and thresher sharks has also been conducted along the east coast of Australia where movements of sharks were largely restricted to the Tasman and Coral Seas (Stevens et al, 2010).…”
mentioning
confidence: 99%
“…Este tipo de natación oscilante ha sido descripto para varios peces como el atún amarillo (Holland et al 1990, Block et al 1997, el atún de aleta azul (Brill et al 2002) y el atún ojudo (Holland et al 1990) y para varias de tiburones como el azul (Carey y Scharold 1990, Klimley et al 2002, el martillo (Jorgensen et al 2009), el mako (Holts y Bedford 1993, Klimley et al 2002, Sepulveda et al 2004, el tigre (Nakamura et al 2011), el zorro (Cartamil et al 2010b), el cazón (West y Stevens 2001), el tiburón ballena (Brunnschweiler et al 2009), el blanco (Bruce et al 2006, Domeier y Nasby-Lucas 2008, Klimley et al 2002, Weng et al 2007, el peregrino (Shepard et al 2006, Sims et al 2003, el dormilón del Pacífico (Hulbert et al 2006) y el de Groenlandia (Stokesbury et al 2005).…”
Section: Movimientos Verticalesunclassified
“…Los movimientos de pequeña escala son variables e influenciados por factores como la dinámica local de presas, características oceanográficas (Cartamil et al 2010b) y tal vez la abundancia de predadores.…”
Section: Movimientos Verticalesunclassified